2021
DOI: 10.1002/pop4.318
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and terrorism in Africa: Understanding the nexus based on existing levels of terrorism

Abstract: Prevailing literature recognizes that poverty may not act as a significant factor that spurs the level of terrorist activities. However, literature on the relationship between poverty and terrorism in Africa remains sparse. This study, therefore, investigates the influence of poverty on terrorism in 26 African countries from 2000 to 2017 in a panel data environment. Findings from the two-stage least square regression, with standard errors which are heteroskedastic and autocorrelation consistent, show that pove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The first lags of the regressors are used as instruments in the original regression to control for simultaneity and reverse causality. This procedure is consistent with the studies of Asongu and Biekpe (2018) and Iheonu and Ichoku (2021a). The instruments are derived through an OLS regression in the model with their first lags.…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…The first lags of the regressors are used as instruments in the original regression to control for simultaneity and reverse causality. This procedure is consistent with the studies of Asongu and Biekpe (2018) and Iheonu and Ichoku (2021a). The instruments are derived through an OLS regression in the model with their first lags.…”
Section: Methodsmentioning
confidence: 74%
“…The region has become a fertile ground for the growth of terrorist activities as a result of a myriad of factors, which include inequality, tribal and ethnic tensions, religious fundamentalism, political instability and armed conflict. Iheonu and Ichoku (2021a) have also revealed that unemployment and bad governance are factors influencing terrorist activities in Africa.…”
Section: Introductionmentioning
confidence: 99%